2014
DOI: 10.1371/journal.pone.0108598
|View full text |Cite
|
Sign up to set email alerts
|

Hard Surface Biocontrol in Hospitals Using Microbial-Based Cleaning Products

Abstract: BackgroundHealthcare-Associated Infections (HAIs) are one of the most frequent complications occurring in healthcare facilities. Contaminated environmental surfaces provide an important potential source for transmission of many healthcare-associated pathogens, thus indicating the need for new and sustainable strategies.AimThis study aims to evaluate the effect of a novel cleaning procedure based on the mechanism of biocontrol, on the presence and survival of several microorganisms responsible for HAIs (i.e. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(156 citation statements)
references
References 56 publications
(52 reference statements)
9
119
0
4
Order By: Relevance
“…Probiotic decontaminants are based on the principle of biological competition, whereby applied solutions replace the bad bacteria with a friendlier version [35,36]. The products contain Bacillus spores (e.g.…”
Section: Probiotic Disinfectantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic decontaminants are based on the principle of biological competition, whereby applied solutions replace the bad bacteria with a friendlier version [35,36]. The products contain Bacillus spores (e.g.…”
Section: Probiotic Disinfectantsmentioning
confidence: 99%
“…The products contain Bacillus spores (e.g. Bacillus subtilis, Bacillus pumilus and Bacillus megaterium), which are termed 'innocuous' since they exert no biocidal activity [36]. These organisms germinate and spread along dry surfaces, thereby inhibiting proliferation survival of other microbial soil.…”
Section: Probiotic Disinfectantsmentioning
confidence: 99%
“…The probiotic-based solution contained 1% of spores (30 × 10 6 CFU/ml) of Bacillus subtilis, Bacillus pumilus and Bacillus megaterium, in addition to ionic surfactants (0.6%), anionic surfactants (0.8%) and enzymes (amylases 0.02%) [18].…”
Section: Sanitizing Solutionmentioning
confidence: 99%
“…Some studies have focused on the potential ability of a biofilm to inhibit bacterial growth on silicone materials used in the urogenital tract [10,11,13,15] oral cavity [12,14] and/or other matrices [10,16]. Recent trials have shown that probiotic bacteria may also be used to sanitize hospital environments in order to combat the increase in nosocomial pathogens [17,18]. Probiotic bacteria (Probiotics in progress/PIPs) are spores of Bacillus spp, and considered to be innocuous microorganisms as, unlike disinfectants, they do not act as biocides.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, обычные дезинфектанты обладают неспецифическим биоцидным дей-ствием, а также связываются с органическими загрязнениями, что влечет за собой вторич-ную контаминацию поверхностей и селекцию устойчивых к антимикробным препаратам па-тогенных штаммов микроорганизмов. Прове-денные зарубежные исследования подтверди-ли отсутствие таких свойств у чистящих препа-ратов на основе пробиотиков [5,6,16,17].…”
unclassified